Contribution of Endogenous Bradykinin to Fibrinolysis, Inflammation, and Blood Product Transfusion Following Cardiac Surgery: A Randomized Clinical Trial. Issue 4 (24th December 2012) - Balaguer, J M; Yu, C; Byrne, J G; Ball, S K; Petracek, M R; Brown, N J; Pretorius, M
<x xml:space="preserve">Abstract</x> Bradykinin increases during cardiopulmonary bypass (CPB) and stimulates the release of nitric oxide, inflammatory cytokines, and tissue‐type plasminogen activator (t‐PA), acting through its B2 receptor. This study tested the hypothesis that endogenous bradykinin contributes to the fibrinolytic and inflammatory response to CPB and that bradykinin B2 receptor antagonism reduces fibrinolysis, inflammation, and subsequent transfusion requirements. Patients (N = 115) were prospectively randomized to placebo, ε‐aminocaproic acid (EACA), or HOE 140, a bradykinin B2 receptor antagonist. Bradykinin B2 receptor antagonism decreased intraoperative fibrinolytic capacity as much as EACA, but only EACA decreased D‐dimer formation and tended to decrease postoperative bleeding. Although EACA and HOE 140 decreased fibrinolysis and EACA attenuated blood loss, these treatments did not reduce the proportion of patients transfused. These data suggest that endogenous bradykinin contributes to t‐PA generation in patients undergoing CPB, but that additional effects on plasmin generation contribute to decreased D‐dimer concentrations during EACA treatment. Clinical Pharmacology & Therapeutics (2013); 93 4, 326–334. doi:10.1038/clpt.2012.249